Revealing the influence of the mode of controlled oscillations of the liquid pool on the surfaced bead geometry - Lebediev, Volodymyr; Novykov, Sergii; Loi, Serhii; Spihtarenko, Volodymyr; Matviienko, Maksym (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates geometric dimensions of the weld bead produced by gas metal arc surfacing with a consumable electrode. Standard surfacing is characterized by low productivity because of the significant number of runs and the need for machining tall beads. Deep penetration causes a significant proportion of the base metal in the surfaced layer and inhomogeneity of the chemical composition. Existing approaches to controlling the geometry of the weld bead (pulsed arc modes, electrode oscillations, electromagnetic arc control) have a limited effect on the width or complicate the design of the welding head. This work considers gas metal arc surfacing with controlled low-frequency oscillations of the workpiece with a liquid weld pool. The installation is built on an adjustable electric drive with a stepper motor with a programmable setting of the frequency and amplitude of oscillations. These parameters, together with energy parameters and speed, affect the geometric dimensions of the weld bead and the mechanical properties of the surfaced metal. The width, height, and depth of the weld bead penetration were determined from macrographic cross-sections. A mathematical model of bead geometry as a function of surfacing parameters has been built by using experimental data regression analysis. The errors in predicting the width and height did not exceed 21.7% and 15%, respectively, thereby confirming its practical applicability. Controlled oscillations were found to increase bead width by a factor of 1.5–2 and reduce bead height by up to a factor of 6 compared with vibration-free surfacing. This is attributed to redistribution of thermal energy and intensification of horizontal melt flows. Changing the weld bead geometry increases surfacing productivity and control accuracy. The method is suitable for use in adaptive welding systems